Optimizing FM broadcast coverage using hybrid optimizations - Mappatao, Gerino P. (Animo Repository, 2011)
Much is saved on energy consumption of an FM broadcast transmitter if the antenna system possesses a radiation pattern that covers only the desired target areas. This paper presents a more accurate and simple method of shaping the azimuth electric field pattern of an antenna system for FM broadcast applications. It uses a uniform linear antenna array of two omnidirectional elements called bays. The radiation pattern of the array is shaped by determining the values of two control factors: the physical distance separating the two bays and their phase relationship. The hybrid combination of Genetic Algorithm (GA) followed by Nelder-Mead optimization processes is used to determine the optimum values of these control factors assuring that the resulting radiation pattern best approximates the desired pattern. The results show that the method can produce patterns that can better resemble the desired patterns than the patterns shaped using GA with optimum GA parameter values. The results of the optimization of the sample patterns are validated using an antenna simulation software. Sample directional patterns and their appropriate applications in specific areas are presented to demonstrate the significance of the method. © 2011 Praise Worthy Prize S.r.l. - All rights reserved.